Quality of glycemic control in assessment of the requirement for insulin in patients with type 2 diabetes and comorbid pathology - Irina A. Kurnikova (Endocrinology Research Centre, 2018)
Background. In modern medicine, several diseases exist that require an interdisciplinary approach, and type 2 diabetes mellitus (DT2), which can be considered as an initially comorbid pathology, is certainly one of these. Reportedly, a high level of comorbidity not only changes the presentation of the disease and makes diagnosis challenging, but in patients with comorbid diseases, the progression of the disease also increases, the prognosis worsens, and approaches to diagnosis and therapy change. For patients with DT2, a significant hallmark in the progression of the disease is the formation of insulin dependence. Determination of the mechanism behind comorbidity affecting the course and progression of diabetes, including the development of insulin dependence, necessitates research. In addition, the mutual influence of the quality of disease management of diabetes and the level of comorbidity also require investigation. Aims. We aimed to assess the influence of the quality of metabolic control and severity of comorbidity on the risk of insulin dependence in patients with DТ2. Materials and methods. A total of 166 patients with DT2 were divided into groups on the basis of the variant of hypoglycemic therapy, which was with either oral hypoglycemic agents or insulin therapy. The diagnostic complex included regular monitoring of glycaemia and the evaluation of the level of comorbidity. Results. The relationship between the quality of disease management and the level of comorbidity was established. With comorbidity measured using the Cumulative Illness Rating Scale (CIRS), a score above 14 points reduced the effectiveness of the therapy and triggered the initiation of more intensive glycemic control. Data on the influence of the quality of glycemic control and the parameters of comorbidity on the risk of insulin dependence in patients with DT2 were obtained. Conclusions. High CIRS scores in patients with DТ2 reduce the likelihood of achieving glycemic control targets. These patients require more intensive self-monitoring (at least four times during the day), and the risk of formation of insulin dependence is increased by 1.5 times.